Event-triggered output regulation of heterogeneous multiagent networks - Meng, Xiangyu (2020)
This technical note addresses the event-triggered output regulation problem of heterogenous multiagent systems. In contrast to similar problems solved by algorithms based on continuous communication between neighboring agents, a distinctive feature of the proposed algorithm is that communication from one agent to another is mediated by the corresponding triggering condition of the link. The output regulation problem is solved by a distributed design of predictors, observers, detectors, and controllers. In addition, positive lower bounds of interevent times for all links are provided. The effectiveness of the proposed algorithm is demonstrated by a numerical example.